Analysis of Maintenance System on Escalators to Extend Service Life at Minangkabau International Airport - Fitri, Annisa Rahmadani; Abu, Risal; Mukhnizar, Mukhnizar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
An escalator is a vertical transportation system designed to move people between two or more levels in a building. The purpose of this study is to determine the working principle of an escalator. To determine the maintenance system, especially on the Motor, Gearbox, Roller step in an escalator. To determine the maintenance actions on the Motor, Gearbox, Roller step in escalator maintenance to extend the service life of the escalator. This study was conducted at Minangkabau International Airport (BIM) using qualitative methods. The results of this study are that the maintenance system for escalator components (Motor, Gearbox, Roller Step) is carried out twice a month using preventive maintenance. Maintenance actions include routine cleaning, checking the condition of the lubricant, lubrication, and testing the function of each component. With appropriate actions, such as changing the lubricant and checking for wear on critical parts, the service life of the escalator can be extended and performance remains optimal.